Consistency of endothelial function across two consecutive oral contraceptive pill cycles - Lindsay A. Lew; Desiree Tugwell; Tess Leavitt; Melanie Vitez; Emily J. Ferguson; Kyra E. Pyke (Experimental Physiology)
Abstract Oral contraceptive pills (OCPs), composed of an active pill (AP; synthetic hormone) and a placebo pill (PP; synthetic hormone‐free) phase, might impact endothelial function across the OCP cycle depending on the synthetic hormone composition (type and dose). Only one study has investigated very low‐dose second‐generation OCP users, finding impaired endothelial function in the AP versus PP phase. No studies have reported individual changes in endothelial function across OCP phases, and no studies have examined repeatability of endothelial function across multiple OCP cycles. Owing to the consistency of synthetic hormone exposure in OCP users, we hypothesized that group and individual flow‐mediated dilatation (FMD) responses to the OCP phase would be consistent across two OCP cycles. Endothelial function was assessed by FMD via Duplex ultrasound in 17 very low‐dose second‐generation OCP users (19 ± 2 years of age) during the AP phase and PP phase for two consecutive OCP cycles. Individual responses were classified using a threshold of ±2 × typical error. There was a main effect of phase such that FMD was lower in the AP versus PP phase (P = 0.022; AP = 4.3% ± 1.3%, PP = 5.4% ± 1.4%). Threshold analysis revealed no consistent responders, and there was no relationship between Δ%FMD in cycle 1 and cycle 2 (P = 0.220; r = −0.314). Overall, these results suggest that exposure to the synthetic hormones in second‐generation OCPs might be detrimental to vascular function, although this was not demonstrated to be a consistent trait‐like response at the individual level over two cycles.